Aplicación de una auditoría ambiental en la empresa “Ecofroz” s.a. de la ciudad de Machachi, cantón Mejía, provincia Pichincha, durante el periodo del 01 de enero al 31 de diciembre del 2012 - Beltrán Freire, Iván Noé (2015)
Has been applied an Environmental Audit, with the main objective of analyzing the environmental risks inside the process of production of the company Ecofroz SA risks and assert their practices compliance with the requirements of environmental policy and determine if this is consistent environmental laws. The evidence found was analyzed using different research methods obtaining the necessary information for the study, through the survey, interview, observation and internal control questionnaires, aimed at workers and employees, which allowed us to know the procedures of the organization, in order to get foundations that allow us to provide a comprehensive view of the organization analyzed. The environmental assessment, there are three files, the planning, the permanent file and the current file; through these, we find the weaknesses and some deficiencies showing the organization, these are detailed in working papers, and through this a final report that will enable the Company Ecofroz SA, make changes and improvements based was developed to evidence found during the evaluation process, thereby improving their productivity performance aimed at environmental protection.